Big Five Personality Types & Knowledge Hiding Behaviour: A Theoretical Framework - Anand, Payal; Jain, Kamal Kishore (Archives of Business Research, 2014)
The paper provides a theoretical framework explaining the relationship between personality types and knowledge hiding behavior. In a knowledge based economy, knowledge is the foundation of a firm’s competitive advantage. Capturing, storing, sharing, and using knowledge has gradually become an integral part of most firms’ knowledge management strategy. Extensive knowledge sharing within organizations still appears to be the exception rather than the rule. Hoarding knowledge and looking guardedly at the knowledge offered by others are natural human tendencies (Davenport & Prusak, 1998). So far, there have been studies on knowledge sharing but knowledge hiding is the area which is still untapped. Moreover, no study has been done to study the relationship between personality types and knowledge hiding behavior. This study, therefore, attempts to fill that research gap by providing a theoretical framework based on literature review. The study uses big five dimensions of personality theory of organization behaviour as it emerged from decades of research and has gained distinct prominence. Limitations and directions for future research are outlined.